Impact of ecotourism development on quality of life of local community at Tasik Kenyir, Malaysia - Mohd Adam, Syamimi (2018)
Tasik Kenyir has huge potential to become a top ecotourism tourist destination in Malaysia as well as worldwide. The particular study at Tasik Kenyir was only focused on tourism operators that engage in ecotourism businesses and tourists perspectives of ecotourism development. The studies on the impact of ecotourism development on quality of life of the local community are still scarce although tourism is one of the important industries in Malaysia. Thus, this study aims to bridge the research gap of investigating impacts of ecotourism development towards quality of life of the local community at Tasik Kenyir. The general objective is to understand the impacts of ecotourism development towards quality of life of local community at Tasik Kenyir. The specific objective of the study is to identify the perception of impacts of ecotourism development at Tasik Kenyir. The study is also to measure the quality of life of local community at Tasik Kenyir. Then, the objective of study is to determine the influences of the perceived impact of ecotourism development towards quality of life of local community at Tasik Kenyir. Besides, the study is also to determine the socio demographic background of the local community at Tasik Kenyir. The local community refers to the villagers from the selected three villages are chosen in this study. A total of 260 local respondents were surveyed over a threeweek period in the three selected villages at Tasik Kenyir, Malaysia. The census data were collected using face-to-face questionnaires. All the questions in the questionnaire were closed-ended questions and Likert scale was used. A descriptive analysis shows that in general the community agrees with the impacts of the ecotourism development in the area. Factor analysis test is to measure the quality of life of local community at Tasik Kenyir. Multiple regression procedures were conducted to determine the causal relationships. The result of the study has distributed accordingly in 11 factors. All the 11 factors were later regrouping into 7 factors only based on similar theme and then named as particular factors which included Good Health, Ecotourism Contribution, Preservation and Conservation,Community Development, Accessibility, Substantial Opportunity and Destination Recognition. In addition, the result of the study also has found that income, distance to the ecotourism site, frequency of vacation, and perceptions on environmental impacts have influence on the quality of life of the local community. The findings of this study can assist tourism stakeholders such as state government of Terengganu, Tourism Terengganu and Central Terengganu Development Authority (KETENGAH) and the community in the implementation of tourism development strategies in the future by determining features that are important and need to be prioritized for improvement in quality of life of local community. The possible economic options for the local community and skill training programs can be identified that are related to the tourism industry to change their quality of life to become better.